Cooking by solar power - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
FAO predicts that the number of people affected by fuelwood shortages will grow to approximately 2.4 billion in ten years' time. One possible solution to the crisis is solar cooking. Robert Metcalf, a microbiologist at California State University...